Birth asphyxia: a major cause of microcephaly in the Calabar, Nigeria - Eyong, Komomo Ibor; E. Ekanem, Emmanuel; A. Asindi, Asindi (International Journal of Contemporary Pediatrics, 2017)
Background: Birth asphyxia is a leading cause of neonatal mortality and survivors are at risk for neurodevelopmental sequelae including motor and cognitive disabilities. Microcephaly is a known consequence of severe birth asphyxia and may be accompanied by abnormalities such as cerebral palsy, seizures, developmental delay and intellectual disability. The work was designed to demonstrate the critical role played by birth asphyxia the causation of microcephaly in our environment. Methods: All children seen in the Neurology Clinic of the University of Calabar Teaching Hospital (UCTH), Nigeria, from January 2014 to December 2014 with a diagnosis of microcephaly (OFC more than 2SD below the normal for the age) were recruited into the study. A detailed antenatal, birth, and developmental history were obtained. Clinical and neurological examinations were carried out. Hearing and vision of patients were assessed. Results: Forty nine (10.5%) of the 465 children seen at the neurologic clinic had microcephaly. Birth asphyxia accounted for 35 (71.4%) of these children. Majority of the children with birth asphyxia were home delivery. Some (34.3%) were born in government approved centers including tertiary care facility. Epilepsy (71.4%) was the most common comorbidity associated with microcephaly. Conclusions: The finding of this study demonstrates the persistent role of birth asphyxia in the aetiology of neurological damage in Nigerian children. The study agrees with previous surveys that severe birth asphyxia is a major cause of microcephaly in our environment in contrast to Western studies where genetic syndromes are predominant causes. Increased effort at preventing birth asphyxia including legislation is advocated.